2016
DOI: 10.1111/dgd.12327
|View full text |Cite
|
Sign up to set email alerts
|

Human gingival fibroblasts induced and differentiated into vascular endothelial‐like cells

Abstract: A novel method for repair of vascular disease, mechanical damage, and tissue rebuilding is urgently required. Vascular endothelial cells (VECs) play an essential role in vascular rebuilding and vasotransplantation. In the present study, human gingival fibroblasts (HGFs) were cultured and induced into endothelial-like cells in vitro in order to confirm that HGFs with stem cell properties possessed the potential for differentiation into endothelial-like cells. The epithelium was extracted from normal human gingi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
1
21
1
Order By: Relevance
“…This is also the focus of this experiment. HGFs have properties similar to stem cells and can induce trans-differentiation into VEC-like cells [12]. Therefore, in this study, VEC-like cells were used as vascularised seed cells for tissue engineered vascularised oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is also the focus of this experiment. HGFs have properties similar to stem cells and can induce trans-differentiation into VEC-like cells [12]. Therefore, in this study, VEC-like cells were used as vascularised seed cells for tissue engineered vascularised oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experiments of our research group [12] showed that the endothelium-like changes in HGFs were most obvious when VEGF 165 concentration was 8 ng/mL and induction time was 35 days. On this basis, VEGF 165 was directly administered at a concentration of 8 ng/mL for induction for 35 days.…”
Section: Induction Of Vascular Endothelial Cells and Tubular Formatiomentioning
confidence: 94%
See 1 more Smart Citation
“…Quercitrin has been used to alter biomarker production, related to periodontal regeneration, in primary human gingival fibroblasts [ 20 ]. Recently, we have found that human gingival fibroblasts are able to differentiate into vascular endothelial-like cells and vascular smooth muscle-like cells [ 21 , 22 ]. These cells have some common characteristics, in that gingival fibroblasts and periodontal ligament stem cells both show high expression of CD73 and CD90 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the endothelium has an important role in the pathogenesis of a variety of systemic pathologies (e.g., hypoxia, metabolic disorders, and atherosclerosis), because it initiates blood coagulation and blood vessel spasm after injury. Structural and functional studies of the endothelium have revealed its crucial role in the pathogenesis of PD [4,8]. Biologically active endothelial cells participate in various mechanisms of homeostasis, including local circulation mechanisms.…”
Section: ключевые слова: остеопороз пародонтит эксперимент эндотелийmentioning
confidence: 99%